2D to 3D solvent mediated transformation of a photoreactive lanthanum MOF: a case of three parallel photo-cycloaddition reactions. Issue 7 (23rd January 2019) - Skoulika, Stavroula; Siskos, Michael G.; Michaelides, Adonis
Abstract : Irradiation of the 3D MOF [La2 (hex)3 (H2 O)4 ]3H2 O, obtained upon dehydration of the layered compound [La2 (hex)3 (H2 O)6 ]9H2 O, gives two [2 + 2] and one [4 + 4] photocycloaddition reactions occurring in the parallel reaction scheme. Abstract : The 3D lanthanum-dicarboxylate MOF [La2 (hex)3 (H2 O)4 ]3H2 O, (1 ), (hex = trans, trans -muconic acid) has been obtained at 50 °C, in a silica gel column, either via in situ transformation of the 2D MOF [La2 (hex)3 (H2 O)6 ]9H2 O, (2 ), published previously, or directly. The structure is made up of metal–ligand layers pillared by a ligand dianion. The comparison of the crystal structures of the two MOFs allowed us to propose a possible mechanism of the 2D to 3D transformation. The presence of many short olefinic contacts allowed the formation of three photoproducts at different yields, the major one being the rtct isomer for the 3D MOF and the rttc one for the 2D MOF. In both cases, the three photoreactions proceed with the parallel reaction scheme. The comparison of the crystal structures of1 and2 allowed the photoreactivity differences observed to be explained.